PENINGKATAN KEDISIPLINAN GURU MELALUI REWARD AND PUNISHMENT DI SDN KETAWANG KARAY I KECAMATAN GANDING KABUPATEN SUMENEP SEMESTER 1 TAHUN 2017/2018 - Ngumpriyatun Ngumpriyatun (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
A learning can be done well if the teacher can behave discipline in following the learning. Discipline is a situation where the teacher adheres to the rules or rules that apply. In attendance, many teachers at Ketawang Karay I Elementary School in Ganding Sub-District, Sumenep District, often come late to school. This causes wasted learning time in the morning. In addition, there are still many teachers in learning who do not make classroom administration and complete other learning. The principal takes steps to correct this condition by conducting school actions to improve the situation. Ways that can be used by principals so that teachers can behave in a discipline are by giving rewards and punishment. Reward And Punishment given by the principal will increase the discipline of teachers in Ketawang Karay I Elementary School, Ganding Sub-District, Sumenep Regency. This research uses action research with the results of increasing teacher discipline through Reward And Punishment in Ketawang Karay I Elementary School, Ganding Sub-District, Sumenep Regency, Semester 1, 2017/2018 can increase. This is evident from the results of the initial conditions, the discipline of the teacher in attendance (the teacher is present on time) there are 3 teachers or 27.27%, increasing again in the first cycle of the teacher's right time there are 7 or 63.64%, and increase again in cycle II to 10 or 90.91%.